HEALTH-IMPROVING PHYSICAL EDUCATION IN THE SECOND PERIOD OF MATURITY AND AMONG ELDERLY PEOPLE (ResearchJet Journal of Analysis and Inventions, 2021)
This article deals with on the basics of frequencies on heart rate in the selection of the second period of maturity and the norm for engaging in healthy physical activity in the elderly. To do this, subtract the age of the practitioner over the years from the maximum number of heartbeats. It is argued that the norm of physical activity, which is performed at the level of 65% to 85% of the result.